FORMULATION AND ANTIOXIDANT ACTIVITY OF COMBINATION OF RED DRAGON FRUIT (Hylocereus polyrhizus) AND GREEN TEA EXTRACT (Camellia sinensis) - Cantika Zaddana; Almasyhuri Almasyhuri; Sara Nurmala; Putri Rizna Noviyanti (Journal of Global Nutrition, 2023)
Red dragon fruit and green tea are plants that can be made as food products that contain catechins needed as antioxidants. This study aims to determine the formula of jam that the panelists like and determine the content of flavonoids and antioxidant activity in jam products. The method of determining flavonoid content was carried out using the aluminum chloride (AlCl3) calorimetry method and antioxidant activity can be measured using the DPPH (1,1- diphenyl-2-picrylhydrazyl) free radical deterrent method by spectrophotometry Uv-Vis. This study used 4 jam formulas which were distinguished from the concentration of green tea extract namely formula 1 (0), formula II (5%), formula III (10%), and formula IV (15%). The parameters measured in this study were panelist like, flavonoid levels, and antioxidant activity. The results of the analysis show that formula 3 is the most preferred formula for panelists based on the average value of the hedonic test. Flavonoid levels of formula 3 jam were 0.0274% and hadantioxidant activity with IC50 of 108.5335